Serving Innovation Well? – Mismatch between the Supply and Demand Side of Services by Innovation Intermediary Organizations in Hungary - Éva Gajzágó (DETUROPE)
Innovation intermediary organizations play a significant role in the national innovation systems as they provide services for the actors of the innovation network. Their main goal is to connect these actors to promote knowledge exploitation and -transfer. In the past 12 years intermediaries were founded and developed in Hungary, however, the effectiveness of their service was not measured comprehensively. This paper presents the main results of an analysis examining the effectiveness of their offered services.